The Use of Aircraft for Reconnaissance Surveys (Polar Record, 1940)
The technique of landing a party in the centre of a totally unmapped area and working from an aeroplane-stocked base has been developed largely by Bradford Washburn in Alaska. In the Alpine Journal for November 1939, p. 213, he makes some interesting remarks in this connection.